Study on consumer satisfaction towards branded consumer non durables a study with reference to rural consumers in kerala - Ram, G.; Markose, B. (university of Jaffna, 2014)
Considering the changing rural consuming system the rural consumers are becoming more concerned about the branded items not only in the case of consumer durables but on non durables also. Hence the study is undertaken with the objective of analyzing the consumer satisfaction towards the non-durables The study was confined to three districts of Kerala representing north, south and central zones covering a sample of 300 rural consumers and analyzed with the help of indices. The study highlights the fact that distribution net work of the producers are seemed to be effective, it is seen that for 'availability' factor consumers recorded highest level of satisfaction for all selected products. It is also noted that for price the level of satisfaction is the lowest, which implies that if the products are offered into low price, there is a scope for expanding market share of the products.
Keywords: Rural consumer; Non-durables; Consumer satisfaction; Reference group